Is teaching bad for your health? New evidence from biomarker data. (2nd January 2022) - Sims, Sam; Jerrim, John; Taylor, Hannah; Allen, Rebecca
ABSTRACT: Teaching is a demanding job and research suggests that prolonged exposure to stress can affect physical health. While some studies have found that teachers do indeed report relatively poor physical health, the existing literature has important methodological limitations. In particular, no research exists comparing teachers to other occupations using objective biomarker data to measure health. We provide such evidence using two datasets: a representative, cross-sectional survey and a longitudinal convenience sample. We find no statistically significant overall association between teaching and physical health in any of our models or datasets. Teaching may therefore not be as bad for physical health as previously thought.